Beyond the 'Right Answer': A Synthesis of Process-Oriented and Authentic Assessment in English Language Education - Dhanan Abimanto; Rahayu Puji Haryanti (Epigram, 2025)
Assessment in English Language Teaching (ELT) is at a critical juncture, moving away from traditional, product-focused evaluation towards more holistic, learner-centered paradigms. This article synthesizes conceptual and empirical literature to argue for an integrated assessment framework grounded in sociocultural learning theory. Traditional assessment methods, often characterized by standardized tests and factual-recall questions, promote a narrow conception of learning, create negative washback effects, and can perpetuate systemic inequities. In response, this article examines an alternative paradigm rooted in Assessment for Learning (AfL), which emphasizes process-oriented, authentic, and performance-based approaches. A systematic review of the literature was conducted, focusing on key pillars of alternative assessment, including performance-based tasks, portfolio assessment, and the mediational roles of feedback, interaction, and scaffolding. The findings indicate that these alternative methods, when unified under a Vygotskian framework of the Zone of Proximal Development (ZPD), are more effective at fostering communicative competence, critical thinking, and learner autonomy. The discussion addresses the pedagogical implications of this framework across the four language skills, confronts the significant implementation challenges, including the need for enhanced teacher assessment literacy and the reality of standardized testing, and considers the ethical dimensions of assessment. The article concludes that a thoughtful integration of process and authentic assessment is not merely a pedagogical choice but a necessary step toward empowering students as confident, lifelong language learners.